Pengaruh Jumlah Uang Beredar Dan Nilai Tukar Rupiah Terhadap Inflasi Di Indonesia (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This study aims to determine the effect of the money supply and the exchange rate on inflation in Indonesia. The theory used in this research is to use the Quantity Theory of Money and the theory of purchasing power parity by David Ricardo. Data used is secondary data from 2005 to 2017. The research was done by using a multiple linear regression. Test the hypothesis using the F test to test the feasibility of the model. The t-test is used to determine the influence between variables. The results of this study showed a significant effect on the amount of money in circulation to iflasi in Indonesia. The exchange rate significant effect on inflation in Indonesia.